Volunteering and self-perceived individual health: Cross-country evidence from nine European countries. Issue 3 (21st February 2020) - Nappo, Nunzia; Fiorillo, Damiano
Abstract : Purpose: The paper studies the simultaneous effect of formal and informal volunteering on self-perceived individual health across nine European countries while controlling, among other things, for socioeconomic characteristics and social and cultural participation. Design/methodology/approach: This paper employs the 2006 wave of the EU-SILC dataset for estimating recursive trivariate probit models using instrumental variables. Findings: The paper finds that although formal volunteering and informal volunteering are correlated with each other, they have different impacts on health. Formal volunteering is never correlated with higher self-perceived individual health except in the Netherlands. In contrast, informal volunteering is related to lower self-perceived individual health in Austria, Finland, France, the Netherlands, Spain, and Italy. Research limitations/implications: The first limitation concerns the absence of other measures of volunteering, such as volunteering hours that are not available in the employed dataset. The second limitation is that the dataset collection on social and cultural variables in EU-SILC is cross-sectional while the optimal dataset should be a panel data. The third limitation is that instrumental variables are observed in the same year of declaring self-perceived individual health while the optimal timing would be at least one year before. Practical implications: Findings of the paper show that formal volunteering has no effect on self-perceived individual health while informal volunteering has negative consequences. Social implications: Volunteering is performed because of an individual decision and could be considered a consequence of how social responsibilities are distributed within countries. Our results show that informal volunteering has a negative effect on health; this is likely to depend on how people manage stress coming from performing this altruistic activity. It is likely that a more cautious distribution of social responsibilities could prevent the negative effects of informal volunteering on health. Originality/value: The originality of the present paper is in simultaneously examining the impact of formal and informal volunteering on self-perceived individual health. Furthermore, most of the existing studies on formal volunteering and health focus on a single country; this paper compares nine European countries characterized by different social, cultural, economic, and institutional features. Finally, the paper addresses the issue of reverse causation. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-11-2017-0548